A deepening freeze: More adults than ever are paying higher-rate tax - Isaac Delestre; Tom Waters (Institute for Fiscal Studies (IFS), 2023)
In April, the UK entered the second year of a six-year freeze in the cash value of income tax thresholds - a policy set to become the single biggest tax-raising measure since the 1970s. This is the latest in a long line of measures (by successive governments) that have hugely increased the scope of higher rates of income tax. In this report, we chart this transformation of the role played by top rates in the UK tax system over a 40-year period.
Keywords: 330; Taxes and benefits; Income taxes; Inflation; Labour supply and workforce; Tax; Trends